You are on page 1of 3

Worked Solutions



(b) (1 + bx) 1 + 6ax + 15a 2 x 2 = 1 + 6ax + 15a 2 x 2 + bx + 6abx 2

Edexcel C4 Paper G
1.

(a)

2 cos t
dy
=
dx
sin t

when t = ,
2

gradient = 0

(2)

x2 +

2.

(a)

15a 2 + 6ab = 24

[B]

Hence a = 2,

=1

y2
=1
4

(3)

(using cover up rule)

4.

(a) = x

d
(tan x)dx
dx

y 21

3.

2y 2 = x tan x + ln cos x + c

c=4

2 y = x tan x + ln cos x + 4

3
ln 9 + ln 6
2

(a) (1 + ax)6 = 1 + 6ax + 15a 2 x 2

(4)

y = 4, x = 0 : 2 4 = 0 + ln 1 + c

4
3
= ln(x 2) + ln(2x + 1) + ln(x + 2)
2
3



3
ln 1 + ln 7 + ln 5
2

 

3
9
26
+ ln
= ln
5
2
7
 
3 9
12
+ ln
= ln
5
2 7

[By parts]

dy = x sec2 x dx

= ln 2 +

(7)

(b)

3
1
1
+
+
dx
x 2 2x + 1 x + 2

b=3

= x tan x tan x dx = x tan x + ln cos x + c

(4)

b = 9 6a
15a 2 + 6a(9 6a) = 24

substitute in [B]

3
1
1
+
+
x 2 2x + 1 x + 2
4

(b)

 y 2

[A]

from equation [A]

(b) using cos2 t + sin2 t = 1,


x2 +

we have 6a + b = 9

when x =

(5)

, 2 y = tan + ln + 4
4
4
4
2
1

2 y = + ln 2 2 + 4
4

2 y = ln 2 + 4
4
2
1

y = ln 2 + 2
8
4
2

1

ln 2 + 2
y=
8
4

(3)

www.XtremePapers.net

Science Exam Papers

(6)

5.

(a)

12
x

12

1
2

1
2

4.8

AO AB = 0


2
1
2 5 = 2 + 10 8m + 64 = 0
m8
8


1
12 + 4 + (2 6) = 14
2

1
(ii) using four trapeziums, I =
12 + 4 + 2(8 + 6 + 4.8) = 13.4
4
(i) using two trapeziums, I =

(b)

12x

(2)

m=9

(b) OC = AB

2
= 5
1


3
dx = 12 ln x = 12 ln 3 = 13.1833 . . .

in (i) % error =

14 13.1833
100 = 6.2%
13.1833

in (ii) % error =

13.4 13.1833
100 = 1.6%
13.1833

(a) AB =

(4)

(OABC is a rectangle)
(1)


7
(c) AC =
7

6.

(2)


1
1
equation of line AC is r = 2 + 7
7
8

(5)

(2)


(d) OB = 3
9

2
5
m8

let angle between diagonals be

1
A 2
8

AC OB = |AC| |OB| cos



3
1

7 3 = 99 99 cos
9
7

3 + 21 63 = 99 cos
B (3, 3, m)

= 113.2
acute angle between diagonals = 67 (nearest degree)

Ed

C4 paper G

www.XtremePapers.net

Science Exam Papers

(3)

7.

(a)

y = 12x e 2 x

8.



dy
dy
+ y 1 + 2y
=0
(a) 4x x
dx
dx

dy
1 1
= 12 e 2 x
dx
2

dy
(2y x) = y 4x
dx

dy
= 0,
dx

24 = e 2 x

y 4x
dy
=
dx
2y x

x = 2 ln 24

(3)

(b) y = 12 2 ln 24 24 = 24 ln 24 24
(c)

d2 y
dx 2
so

(1)

(b) at (2, 6) gradient of curve =

(d) area =

equation of normal is y + 6 = 1(x 2)

< 0 and the stationary point is a maximum.

dx 2

1
12x e 2 x

6 8
=1
12 2

gradient of normal = 1

1 1
= e2x
4

d2 y

(4)

x+y+4=0

(1)

(3)

(c) gradient = 0 where y = 4x


1 4
dx = 6x 2 2e 2 x
2

substitute y = 4x into equation of curve.


2x 2 x 4x + 16x 2 = 56 x = 2

= 96 2 e2 (24 2e) = 72 + 2e(1 e)

(5)

Ed

gradient = 0 at (2, 8)

and

(2, 8)

C4 paper G

www.XtremePapers.net

Science Exam Papers

(5)